A Critical Review on Safi Pirlooje’s Diachronic Narrative Study: On the Rhetorics of Persian Folktales and Literary Fictions - Abolfazl Horri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper aims to look at the form and the content of a book entitled, A Diachronic Narrative Study: On the Rhetorics of Persian Folktales and Literary Fictions (Safi, 20015) in a much more critical way, taken mostly from the narratological approaches. Firstly, the main four chapters of the book are reviewed. The first chapter introduces the concept of “Metalepsis”, taken from Genette (1980, 1988). It is said that the writer has made no good effort to support his claims on this concept. The second chapter discusses “Ravayatgardani”, i.e, a change in the process of narration, but again the writer has not been successful in the categorization of Revayargardani. The third chapter has taken the second pronoun into consideration. Finally, the writer has gone to study the hypothetical focalization in chapter four, and has been successful to a large extant in dealing with such a concept. At the same time, some claims are made for and against of what the writer has stated within each chapter. While appreciating the efforts made by the writer all through the analysis of the book, some suggestions are made for the writer to take into his consideration.